The validity of the Strengths and Difficulties Questionnaire (SDQ) for children with ADHD symptoms - Hall, Charlotte L.; Guo, Boliang; Valentine, Althea Z.; Groom, Madeline J.; Daley, David; Sayal, Kapil; Hollis, Chris (PloS one, 2019)
The Strengths and Difficulties Questionnaire (SDQ) is widely used to assess child and adolescent mental health problems. However, the factor structure of the SDQ is subject to debate and there is limited evidence investigating measurement equivalence invariance (ME/I) between treatment groups, informants, and across time. A randomised controlled trial (RCT) recruited 250 participants (6-17 years) who had been referred for an attention deficit hyperactivity disorder (ADHD) assessment. Participants and their clinician either received or did not receive a QbTest report (computer task measuring attention, impulsivity and activity). Parents and teachers completed the SDQ at baseline and 6-months later. This study aimed to understand the factor structure of the SDQ in a clinic referred ADHD sample, and validate the scale as a screening/diagnostic aide and as a measure of treatment outcome both in clinical and research settings. Exploratory Structural Equation Modelling (ESEM) was performed to examine the factor structure, and ME/I was assessed between treatment groups, informants, and time points. The criterion validity of the SDQ predictive algorithm for ADHD was compared with clinician and research diagnoses using logistic regression and tests of diagnostic accuracy. A 5-factor structure provided the best fit with strong factorial invariance between treatment groups and across time points, but not across informants (parent and teacher ratings). SDQ ratings of 'probable' hyperactivity disorder were good predictors of clinical (OR = 10.20, 95%CI 2.18-48.71,p = 0.003) and research diagnoses of ADHD (OR = 6.82, 95%CI 1.95-23.84,p = 0.003), and research diagnoses of Hyperkinetic disorder (OR = 4.02, 95%CI 1.13-14.25,p = 0.031). Further examination of the SDQ hyperactivity 'probable' rating showed good specificity (84.5%-74.5%) but poor sensitivity (45.0-42.5%) for ADHD. The findings indicate the SDQ is a valid outcome measure for use in RCTs and clinical settings. However, care should be taken when using the SDQ predictive algorithm to screen for ADHD in clinically referred samples.